Pajak Pusat dalam Pembangunan dan Pertumbuhan Ekonomi Nasional - Vebrina Hania Cholily (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Tax is the largest revenue of a country, especially the State of Indonesia. Nearly 75% of state revenues currently come from taxes. However, the willingness to pay taxes is still lacking. This is because the public never knows the concrete form of reward from the money spent to pay taxes. This research is a case study with the method of documentation and descriptive analysis. For the data used, namely qualitative and quantitative data. The results of this study are that tax revenue from 2008 - 2018 as a whole increases every year. This increase occurred not only due to the increasing growth in economic activity, improving economic conditions and increasing awareness of taxpayers but also regarding tax regulations such as tax amnesty, tax surveys to find new taxpayers. As well as the occurrence of tax reductions caused by several policies and world economic conditions.